Identification and characteristics of a novel aminoglycoside phosphotransferase, APH(3′)-IId, from an MDR clinical isolate of Brucella intermedia. (30th July 2021) - Lu, Wei; Li, Kewei; Huang, Jiansheng; Sun, Zhewei; Li, Aifang; Liu, Hongmao; Zhou, Danying; Lin, Hailong; Zhang, Xueya; Li, Qiaoling; Lu, Junwan; Lin, Xi; et al.
Abstract: Objectives: To describe a novel chromosomal aminoglycoside phosphotransferase named APH(3′)-IId identified in an MDR Brucella intermedia ZJ499 isolate from a cancer patient. Methods: Species identity was determined by PCR and MALDI-TOF MS analysis. WGS was performed to determine the genetic elements conferring antimicrobial resistance. Gene cloning, transcriptional analysis and targeted gene deletion, as well as protein purification and kinetic analysis, were performed to investigate the mechanism of resistance. Results: APH(3′)-IId consists of 266 amino acids and shares the highest identity (48.25%) with the previously known APH(3′)-IIb. Expression of aph(3′)-IId in Escherichia coli decreased susceptibility to kanamycin, neomycin, paromomycin and ribostamycin. The aph(3′)-IId gene in ZJ499 was transcriptionally active under laboratory conditions and the relative abundance of this transcript was unaffected by treatment with the above four antibiotics. However, deletion of aph(3′)-IId in ZJ499 results in decreased MICs of these drugs. The purified APH(3′)-IId showed phosphotransferase activity against kanamycin, neomycin, paromomycin and ribostamycin, with catalytic efficiencies ( k cat / K m ) ranging from ∼10 5 to 10 7 M −1 s −1 . Genetic environment and comparative genomic analyses suggested that aph(3′)-IId is probably a ubiquitous gene in Brucella, with no mobile genetic elements detected in its surrounding region. Conclusions: APH(3′)-IId is a novel chromosomal aminoglycoside phosphotransferase and plays an important role in the resistance of B. intermedia ZJ499 to kanamycin, neomycin, paromomycin and ribostamycin. To the best of our knowledge, APH(3′)-IId represents the fourth characterized example of an APH(3′)-II enzyme.